Performance of the S-band stratospheric decoding system at the Arecibo Observatory - Woodman Pollitt, Ronald Francisco (1989)
The·objective of OUT work is to propase end analyze a decoding procedure useful to achieve unprecedented spatial and temporal resolution in CW S-band radar measurements at the AO. We find that using hard limiting transformations of the detected echoes (to achieve computational speed) does not distort significantly the process of spectral estimation. Moreover our procedure is efficient in the sense that statistical accuracy of individual estimates is kept with small increase in (coherent) integration time specially if the time series is oversampled. These characteristics make our estimation method very convenient.